UNIVERSITY STUDENTS’ PERCEPTIONS OF AI-INTEGRATED FLIPPED CLASSROOM IN ELT - Jannah, Andi Mir’atul; Mar’ah, Afifatul; Sunra, La; Mansyur, Mansyur; Aeni, Nur (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2026)
This study examines the growing integration of artificial intelligence (AI) in English Language Teaching (ELT), particularly in flipped classroom environments, and explores how students perceive its use in higher education. A qualitative case study design was employed to gain an in-depth understanding of students’ experiences in an AI-supported flipped classroom setting. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that AI serves as an effective support tool for pre-class learning, enabling students to understand materials by summarizing texts, simplifying complex explanations, and improving vocabulary comprehension. Additionally, integrating AI enhances students’ Engagement, learning readiness, motivation, and curiosity, as students become more active in classroom discussions after preparing in advance. However, several challenges were identified, including inaccuracies in AI-generated information, the need for verification, overreliance on AI tools, and technical limitations. In conclusion, while AI-integrated flipped learning offers meaningful opportunities to support independent and active learning, its implementation requires responsible, critical use. These findings provide practical insights for educators in designing effective AI-supported flipped classrooms in higher education.